الأثر التكتوني على نهوض المصاطب النهرية في جنوب السلسلة الساحلية–سورية (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2017)
تشكل دراسة المصاطب الرباعية في جنوب السلسلة الساحلية , منطقتي صافيتا ومرمريتا, أهمية كبيرة في فهم الظروف الجيولوجية والبنيوية التي سادت في المنطقة في تلك الفترة . كان لنهري الابرش والعروس الدور الأكبر في تشكل هذه المصاطب الرباعية التي امتد عمرها من الرباعي الأدنى وحتى الهولوسين . توزعت هذه المصاطب على مساحة ضيقة ونقاط موزعة على حوضي النهرين في جنوب السلسلة الساحلية.قدمنهوض هذه المصاطب مؤشرا قوياً على النشاط التكتوني الذي تمثل بنهوضاتٍ تراوحت بين عشرات ومئات الأمتار، تعرضت لها المنطقة في الزمن الحديث، بالمقارنة مع مدى ارتفاع مصاطب أحواض أنهار أساسية مثل نهر الفرات والكبير الشمالي, وذلك في ضوء الدراساتالليتولوجيةوالستراتيغرافية المنفذة واستخدام تقنيات تحديد المواقع لمعرفة ارتفاعها،ومقارنتها بجداول عالمية لتحديد تأثير التكتونيك على المنطقة آنذاك، وتقديم نموذج رقمي يربط بين النشاط التكتوني ونهوض المصاطب.The study of Quaternary terraces in the south of the coastal chain, safita and Marmaritadistrict, constitute a great importance in understanding the geological and structural conditions, that prevailed in the region in that period. The rivers Abrash andAL-Arousplayed a major role in the formation of these quaternary terraces from the lower Quaternarytill Holocene. These terraces were distributed on a narrow space and points spread over the basins of the rivers in the south of the coastal chain. The high of these terraces, between tens to hundreds meters, are a strong indicator of the advancement of theuplift movements affecting the region in recent times, compared with the uplift of that terraces of other important riverssuch the Euphrates and Nahr El-Kabir-Ash-Shemaliriver,according to thestratigraphy and lithology studies, using GPStechniques to determinethe sites high et compare these values with global data, and then appreacitethe tectonic effect on the region. A numerical model tectonicactivity– terraces uplift is proposed.